Rethinking the foundations of statistics - Kadane, Joseph B.; Schervish, Mark J.; Seidenfeld, Teddy (Cambridge [England] ; New York : Cambridge University Press, 1999)
The book is important collection of essays is a synthesis of foundational studies in Bayesian decision theory and statistics.
Includes bibliographical references and indexes.
uaj 03/03/2015
Loan
Keywords: Bayesian statistical decision theory